Structural violence and colonial oppression in Shahnaz Bashir’s Scattered Souls - Bashir, Ishrat (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper aims to analyse the concept of structural violence and its implications for people as depicted in Scattered Souls. Galtung’s concept of Structural violence and its distinction from other types of violence provides a useful framework to examine and understand the complexity of the representation of violence and socio-political relations. According to Galtung, structural violence refers to the indirect violence inherent in dominant social structures like systemic discrimination based on race, ethnicity, religion, and gender, which create conditions of disadvantage for underprivileged and oppressed people. This paper aims to analyse how the conventional focus on visible violence in Scattered Souls leads to the invisibility and oblivion of implicit or structural violence. This paper endeavours to use Galtung's and Žižek's categorisation of violence as a conceptual tool to understand the impact of violence at the deeper levels. It further seeks to examine the ways in which structural violence deteriorates the lives of people, bolsters the direct violence of occupation, and diminishes the possible impact of resisting oppression.